Differences in the therapeutic effects of high-intensity focused ultrasound (HIFU) ablation on uterine fibroids with different shear wave velocity (SWV): a study of histopathological characteristics. (1st January 2020) - Zhang, Dan-Ling; Wu, Song-Song; Chen, Sheng; Liu, Xin-Xiu; Tang, Jian-Qing; Lin, Ning; Ding, Gui-Sheng; Li, Guo-Ping
Abstract: Objective: To explore correlations between the therapeutic effect of high intensity focused ultrasound (HIFU) and histopathological characteristics of uterine fibroids with different Shear Wave Velocity (SWV) values. Methods: A retrospective study was conducted on 36 women (43 fibroids) who had undergone high intensity focused ultrasound (HIFU) uterine fibroids ablation between January 2019 and January 2020. Preoperative fibroids tissue sections were obtained for histopathological examination. The pathological sections were stained with Masson-trichrome, and were observed and imaged under a Low-power microscope (4 × 10), while the smooth muscle cell (SMC) and collagen fiber content were semi-quantitatively measured. Preoperative fibroid SWV was measured using the Virtual Touch tissue quantification (VTQ) technique. Within one month after HIFU ablation, all patients had undergone a pelvic cavity MRI examination, which measured the size, volume, and non-perfused volume (NPV) of the fibroids. The formula: the ablation rate = NPV/target fibroid volume × 100% was used to calculate the ablation rate of the uterine fibroids. Correlation analysis of SWV values, HIFU ablation rate, along with the smooth muscle cell (SMC) and collagen fiber content, were conducted using the Spearman's correlation test. Results: The collagen fiber and SMC content of the preoperative fibroids were 32.09 ± 15.90 %/view and 37.61 ± 15.32 %/view, respectively. Preoperative fibroid SWV value was 3.56 ± 0.71  m/s. Preoperative fibroid SWV was negatively correlated with SMC content ( r = −0.445, p = 0.003 ), but positively correlated with collagen fiber content ( r = 0.454, p = 0.002 ). The ablation rate was negatively correlated with collagen fiber content ( r = −0.377, p = 0.013 ), but positively correlated with SMC content ( r = 0.402, p = 0.007 ). Conclusion: Differences in histopathological characteristics may be important factors that induce differences in the therapeutic effects of HIFU ablation on uterine fibroids with different SWV values.